Comparative Analysis of Hematological and Inflammatory Biomarkers in Moderate and Severe COVID-19 Patients - Maimun Zulhaidah Arthamin; Mistriono Mistriono; Fani Pradhytasari; Nasrullah Nasrullah; Sonia A Islami; Nanditya I Faramita (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
In COVID-19 patients, abnormal blood clotting is common, characterized by elevated D-dimer and fibrinogen levels, reduced platelets, and prolonged clotting times. The second week of infection can trigger a cytokine storm, marked by heightened proinflammatory Interleukin-6 (IL-6) levels, associated with Acute Respiratory Distress Syndrome (ARDS) and organ failure. This study compared hematological biomarkers, D-dimer, and IL-6 in moderate and severe COVID-19 cases. In a cross-sectional study, 81 patients meeting inclusion criteria were examined at a leading private COVID-19 referral hospital in Malang Regency. Data from clinical records and lab results encompassing blood counts, D-dimer, and IL-6 levels were collected. D-dimer was assessed through immunoturbidimetry (STA-Procoag-PPL, Diagnostica Stago S.A.S.), while IL-6 was measured using a chemiluminescent immunoassay (Cobas e411 Elecsys, Roche). Data distribution normality was assessed using Kolmogorov-Smirnov and Shapiro-Wilk tests. Non-normally distributed data were analyzed using the Mann-Whitney U test for numerical data and the Fisher exact test for comorbidity-severity correlation. Moderate COVID-19 cases disproportionately affected females, while severe cases had an even gender distribution. The median age was comparable, but mild cases were typically younger. Hemoglobin, hematocrit, leukocyte, neutrophil, platelet, and procalcitonin levels were normal in both groups, with lowered lymphocyte counts. Severe cases displayed a higher Neutrophil-to-Lymphocyte Ratio (NLR). D-dimer and IL-6 were significantly elevated in extreme cases. This study underscores potential gender and age-related discrepancies in COVID-19 severity, emphasizing the significance of monitoring specific blood parameters for disease progression indicators. Further investigation is vital to unveil underlying mechanisms and clinical implications, aiding the management of COVID-19 patients.